Acute mechanical and metabolic responses to different resistance training protocols with equated volume load - Sánchez-Moreno, M.; Rodiles-Guerrero, L.; Rendeiro-Pinho, G.; Prieto-Veloso, A.; Pareja-Blanco, F. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To investigate the effect of different resistance training protocols with equated volume load on acute mechanical and metabolic responses. Methods: In a randomized order, 18 men performed 8 different training protocols in the bench press exercise consisting of (sets, repetitions, intensity, and interset recoveries) 3 × 16, 40% 1-repetition maximum (1RM), 2 and 5 minutes; 6 × 8, 40% 1RM, 2 and 5 minutes; 3 × 8, 80% 1RM, 2 and 5 minutes; and 6 × 4, 80% 1RM, 2 and 5 minutes. Volume load was equalized between protocols (1920 arbitrary units). Velocity loss and effort index were calculated during the session. Movement velocity against the 60% 1RM and blood lactate concentration pre-post exercise were used to assess the mechanical and metabolic responses, respectively. Results: Resistance training protocols performed with heavy load (80% 1RM) resulted in a lower (P < .05) total number of repetitions (effect size = -2.44) and volume load (effect size = -1.79) than the scheduled ones when longer set configurations and shorter rest periods were used in the same protocol (ie, higher-training-density protocols). Protocols including a higher number of repetitions per set and shorter rest times induced higher velocity loss, effort index, and lactate concentrations than the rest of the protocols. Conclusions: Our results suggest that resistance training protocols with similar volume load but different training variables (ie, intensity, number of sets and repetitions, rest between sets) produce different responses. Implementing a lower number of repetitions per set and longer rest intervals is recommended to reduce the intrasession and postsession fatigue.